Moderate heritability of hepatopancreatic parvovirus titre suggests a new option for selection against viral diseases in banana shrimp (Fenneropenaeus merguiensis) and other aquaculture species. Issue 1 (December 2016) - Phuthaworn, Chontida; Nguyen, Nguyen; Quinn, Jane; Knibb, Wayne
Abstract Background In shrimp farming, major production losses are caused by viruses. Hepatopancreatic parvovirus (HPV) is one of the viral pathogens that infect banana shrimp (Fenneropenaeus merguiensis ). HPV is thought to slow down growth and cause mortality in the juvenile stages of banana shrimp. Genetic improvement through selection of shrimp resistant to viral diseases is one approach to address this issue. This is the first detailed report on an aquaculture species that investigates whether viral titre varies among families and is heritable, and thus whether viral titre per se is a possible candidate trait for selection to produce resistant stock. Results HPV titre was measured by quantitative polymerase chain reaction of DNA extracted from 1137 offspring (from 48 full-sib families). Estimated heritability of HPV titre, based on the linear animal mixed model, was moderate (h2 = 0.41). Genetic correlations of HPV with body traits (weight, length and width of body, head and tail) ranged from −0.13 to −0.38. HPV titre was negatively correlated with raw and cooked body colour (−0.33 and −0.43, respectively). Conclusions This is the first study based on a large dataset that provides evidence that viral titre may have a genetic component in penaeid shrimp or even in any aquaculture species. The moderate heritability estimated for this trait suggests that resistance to HPV may be achieved by selecting for low HPV titre. With moderate and negative correlations, selection for resistance to HPV should gradually improve body traits and colour of banana shrimp.